The impact of chronic obstructive pulmonary disease in patients' lives: The perception of the health professionals. (8th November 2020) - Rafaelli de Carvalho, Débora; Araújo de Castro, Larissa; Morita, Andrea Akemi; Loyola, Walter Sepúlveda; Fujisawa, Dirce Shizuko; Probst, Vanessa Suziane
Abstract: Introduction: The perception of health professionals about chronic obstructive pulmonary disease (COPD) has not been thoroughly investigated. Objective: To analyze the perception of health professionals about the impact of COPD on the lives of affected individuals. Materials and methods: Qualitative and cross‐sectional study with five health professionals: two nurses, two physiotherapists, and one medical doctor. They participated in a focus group (FG) session, with semistructured questions covering: definition of COPD, activities of daily living (ADL), and physical activity of daily living (PADL), as well as the importance of these outcomes in the lives of individuals with COPD. Data analysis: The FG was recorded, transcribed, and analyzed according to the content analysis. Results: The FG highlighted four main themes: physical‐functional and emotional impairment of individuals, the importance of patient‐health professional contact, repercussions of COPD on the patients' physical activity, and strategies for promoting physical activity. Based on the four themes exposed, the health professionals reported that there is a progression in the lives of individuals' with COPD, which is divided into three phases: adaptation, reluctance, and dependence. Conclusion: There was a negative perception of the health professionals regarding the functionality and emotion of patients with COPD. Emotional aspects, family support, and architectural structure can positively or negatively influence patients' ADL and PADL. Finally, there was a perception of progression in the life of patients with COPD, since their initial adaptation, evolving to physical and emotional dependence.